OP0057 Idiopathic Inflammatory Myopathy is Associated with an Increased Risk of Cardiovascular Events in the First Five Years After Diagnosis. (9th June 2015) - Parraga Prieto, C.; Galloway, J.; Ibrahim, F.; Campbell, R.; Chinoy, H.; Gordon, P.
Abstract : Background: The idiopathic Inflammatory Myopathies (IIM) are chronic inflammatory muscle disorders with significant morbidity and mortality. An increased risk of coronary artery disease and arterial events has been reported in patients with IIM, representing an important cause of mortality. However, there is heterogeneity of findings amongst published articles and a scarcity of population-based studies specifically addressing the comparative risks of cardiovascular (CV) disease in IIM compared to other autoimmune diseases. Objectives: (1) To estimate the incidence of cardiovascular disease in a myositis cohort compared to patients with rheumatoid arthritis (RA) and the general population; (2) To explore the relative contribution of traditional CV risk factors to any difference observed. Methods: A prospective matched population-based cohort study was conducted using UK Clinical Practice Research Database (CPRD) from 1987 to 2013. Subjects with at least two read codes for dermatomyositis or polymyositis were included as the index cohort. As case validation for rarer diseases is an important limitation of the CPRD, detailed validation of IIM was undertaken by the authors, classifying cases as either unlikely, probable or definite based upon clinical and laboratory features, record of muscle biopsy, electromyography and immunosuppressive therapy. In addition, participants with other autoimmune diseases or conditions that might provide a differential diagnosis for IIM were excluded. RA subjects and healthy controls were matched 4:1 on observational window, age and gender. The incidence of CV events was calculated for each cohort over time and compared using Cox proportional hazards models. Multivariable analyses were used to adjust for traditional CV risk factors. Results: A total of 1013 patients with IIM, 4047 RA and 4061 healthy controls were available for analysis. 603 of the IIM cases were considered probable or definite and included in subsequent analyses. The overall rate of CV events was comparable between IIM and RA, both of which had a significantly increased rate compared to the general population (see table II ). However, the event rate in the IIM cohort varied over time. Compared to the general population, in the first five years after diagnosis, the hazard ratio (HR) for CV events was greater in IIM cohort [HR 1.99; 95% confidence interval (CI) 1.51–2.61, p<0.001], but beyond five years this comparative risk declined (HR 0.92, 95% CI 0.40–2.10, p=0.842). In contrast, the increased CV event rate in RA population was higher from the outset and remained elevated throughout the follow-up period. In multivariate analysis the increased HR in the IIM cohort remained significant (p=0.007), suggesting that the excess risk early on cannot be explained entirely by traditional CV risk factors. Conclusions: IIM is associated with an increased risk of CV events in the first five years after diagnosis. The magnitude of risk in this period is greater that observed in RA. Beyond five years the risk appears to return to that of the general population. These findings have implications for patient management and future research. Acknowledgements: Rachael Boggon, CPRD. Disclosure of Interest: None declared